2001
DOI: 10.1007/s002130100879
|View full text |Cite
|
Sign up to set email alerts
|

Effects of harmine on dopamine output and metabolism in rat striatum: role of monoamine oxidase-A inhibition

Abstract: In vivo microdialysis was used to investigate the effects of acute injections of harmine on extracellular concentrations of dopamine, 3,4-dihydroxyphenylacetic acid (DOPAC), homovanillic acid (HVA), and 5-hydroxindoleacetic acid (5-HIAA) in the striatum of awake rats. Administration of harmine in doses of 0.5, 2.5, and 10 mg/kg (i.p.) elicited a dose-dependent increase of the dopamine efflux to 152, 173, and 243% and a decrease in DOPAC to 52, 36, and 10%, and HVA to 67, 45, and 20% throughout, respectively; 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 23 publications
0
36
1
Order By: Relevance
“…The similar effect of genotype on HVA and 5-HIAA is not surprising since the concentrations of these two metabolites are highly correlated (r = 0.63, P < 0.0001). However, the genotype effects we observed on CSF HVA and, to a lesser extent, on 5-HIAA, were in a direction opposite to expectations based on in vitro studies of allele-associated enzyme expression; 12,14 although MAOA inhibitors are known to decrease monoamine metabolite levels, 1,44 in our sample it was the genotype conferring high, rather than low, MAOA activity that was associated with lower HVA levels. One obvious explanation for the correlation of low MAOA activity genotypes to high CSF HVA is that it is simply a chance finding.…”
Section: Discussioncontrasting
confidence: 99%
“…The similar effect of genotype on HVA and 5-HIAA is not surprising since the concentrations of these two metabolites are highly correlated (r = 0.63, P < 0.0001). However, the genotype effects we observed on CSF HVA and, to a lesser extent, on 5-HIAA, were in a direction opposite to expectations based on in vitro studies of allele-associated enzyme expression; 12,14 although MAOA inhibitors are known to decrease monoamine metabolite levels, 1,44 in our sample it was the genotype conferring high, rather than low, MAOA activity that was associated with lower HVA levels. One obvious explanation for the correlation of low MAOA activity genotypes to high CSF HVA is that it is simply a chance finding.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, harmine was once used as an anti-parkinsonian agent and was soon abandoned for its disappointing effectiveness [6]. Harmine and harmaline showed special affinity to the central nervous system (CNS) and exhibited extensive bioactivities such as multi-enzymes inhibitions including monoamine oxidaze type-A [7,8], cyclin-dependent kinases [9], N-acetyltransferase [10] and Na-K ATPase [11], cytotoxicity and antitumour activities [12,13], anti-bacterial activity [14], antiplasmodial activity [15], antileishmanial activity [16], immunomodulator properties [17], temperature-lowering effect [18], cardiovascular actions [19] and so on. Recent research reported that the alkaloids showed potential inhibitory effects on the acetylcholinesterase (AChE) activity using an in vitro thin-layer chromatography (TLC)-bioautographic assay, and ten alkaloids isolated were evaluated based on their inhibitory ability [20].…”
Section: Introductionmentioning
confidence: 99%
“…␤-Carbolines modulate the levels of amine neurotransmitters and their metabolites in the central nervous system (Iurlo et al, 2001), inducing behavioral changes. MAO inhibition also leads these ␤-carboline alkaloids to induce hypothermic effects, probably through a serotonergic mechanism (Abdel-Fattah et al, 1995).…”
mentioning
confidence: 99%